Efektivitas Model POE Berbasis Multi Representasi terhadap Keterampilan Proses Sains Peserta Didik Fase B - Indra Astradika; Ruswandi Hermawan; Aprilia Eki Saputri (Journal on Education, 2024)
Science learning should be accompanied by science process skills. However, factual conditions in the field show that science learning is not optimal in supporting the achievement of science process skills in the indicators of predicting, grouping, concluding, and communicating owned by students. In addition, research that discusses the effectiveness of the Predict Observe Explain (POE) model based on Multi Representation on Science Process Skills is very rare, so researchers apply the POE model based on Multi Representation to the material of the form of matter and its changes. The purpose of this study was to determine the effectiveness of the POE model on the science process skills of phase B students. This study uses a quantitative approach with a One Group Pretest Posttest research design. The population in this study were phase B students in Bojongsoang District. The sample selection used a purposive sampling technique with the selected sample being class IVC SDN X Bojongsoang District, Bandung Regency, totaling 29 people. The instruments used were tests and observation sheets. Data analysis used was the normality test, the mean difference test with the Wilcoxon Test, and the N-Gain Test. Based on the data obtained, there was an increase between the pre-test average and the post-test average, from 46.75 to 77. Based on the mean difference test, a significance value of 0.000 <0.05 was obtained, which indicates that the POE model based on multi-representation is effective for the science process skills of phase B students.